Multicloud-Powered Agriculture: Enhancing Precision Farming Through IoT and Data Analytics - Abhishek Kumar Sinha (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Multi-cloud architectures are revolutionizing modern agriculture through enhanced precision farming capabilities and optimized resource utilization. These systems integrate Internet of Things (IoT) devices, advanced analytics, and machine learning technologies to transform traditional farming practices. The architecture encompasses comprehensive data collection from soil sensors, weather stations, drone imagery, and agricultural machinery, processed through distributed computing platforms. Deep learning models enable accurate crop yield predictions, early disease detection, and resource optimization. Data confidentiality and operational efficiency are maintained through the use of advanced security frameworks and regulatory compliance methods. Through automated decision-making and real-time monitoring, this technology integration shows notable gains in crop yields, resource conservation, and overall farming productivity.